2022
DOI: 10.1002/adfm.202112432
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ionic Diodes with High Rectifying Ratio and Wide Temperature Tolerance

Abstract: Soft iontronics expand the toolbox of bio‐integrated or bio‐interfaced devices, owing to their natural resemblance with living systems; however, the development for analogous integrated ionic circuits is immature due to the difficulty of fabricating fundamental ionic logic elements. Among these, ionic diodes have motivated great endeavors for their unique ionic current rectifying characteristics. Nonetheless, it is still challenging to achieve high‐performance ionic diodes; also, most reported aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
(46 reference statements)
0
17
0
Order By: Relevance
“…With the rapid development of big data and the Internet of Things, more advanced and intelligent wearable electronic devices must be urgently developed to meet new requirements 1–3 . Flexible and stretchable sensors are essential components in wearable electronic devices, and they have attracted increasing interest for their versatile applications, such as in soft robots, healthcare, and human–machine interfacing facilities, owing to their repeatable electrical changes and high sensing sensitivity 4–8 . Conductive hydrogels with high conductivity, flexibility, and adjustable mechanical properties and comprising hydrophilic three‐dimensional polymer networks swollen with a large amount of water are ideal candidates for soft conductors for assembling wearable sensors 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of big data and the Internet of Things, more advanced and intelligent wearable electronic devices must be urgently developed to meet new requirements 1–3 . Flexible and stretchable sensors are essential components in wearable electronic devices, and they have attracted increasing interest for their versatile applications, such as in soft robots, healthcare, and human–machine interfacing facilities, owing to their repeatable electrical changes and high sensing sensitivity 4–8 . Conductive hydrogels with high conductivity, flexibility, and adjustable mechanical properties and comprising hydrophilic three‐dimensional polymer networks swollen with a large amount of water are ideal candidates for soft conductors for assembling wearable sensors 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…The feasible temperature range of diodes is actually important for their practical application. [ 21 ] For the pseudocapacitor diode, the EIS test shows that the slope of the low‐frequency range increases as the temperature rises (Figure 3g), which also means that the ionic conduction of the device is accelerated. As displayed in Figure 3h, as the temperature rises, the capacity and RR II hardly decay, even at 60 °C (the capacity remains at 100.1% of that at 20 °C and the RR II remains at 0.85).…”
Section: Resultsmentioning
confidence: 99%
“…Guo et al reported an integrated temperature-resistant and flexible hydrogel ion diode with a triboelectric nanogenerator [ 60 ]. The diode is highly rectified by a binary ethylene glycol/water solvent system and can work from −20 °C to 100 °C.…”
Section: Recent Progress In Structural Design For Self-powered Systemsmentioning
confidence: 99%